2020
DOI: 10.1111/petr.13964
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐adapted therapy for the management of cytokine release syndrome in children undergoing unmanipulated haploidentical stem cell transplantation

Abstract: Background:We aimed to describe an algorithm for the management of cytokine release syndrome (CRS) associated with haploidentical hematopoietic stem cell transplantation (haploSCT). Patients and methods:We performed a prospective study where children up to 18 years of age undergoing haploSCT with post-transplant cyclophosphamide from September 2014 to March 2020 were included. Supportive care included low-dose adrenaline, high-flow nasal cannula, and N-acetylcysteine (NAC). Methylprednisolone and tocilizumab w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…In the current study, haplo-fever was defined as fever early after PBSC infusion, specifically from day 0 to day +6, because fever together with most cytokines decreased to baseline level right after PTCy. Notably, however, other studies have included patients with CRS-associated symptoms until the peri-engraftment period ( 10 , 13 ), in which case patients with engraftment syndrome or early-onset aGvHD may not be able to be ruled out. Third, cytokine elevation was not associated with aGvHD in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, haplo-fever was defined as fever early after PBSC infusion, specifically from day 0 to day +6, because fever together with most cytokines decreased to baseline level right after PTCy. Notably, however, other studies have included patients with CRS-associated symptoms until the peri-engraftment period ( 10 , 13 ), in which case patients with engraftment syndrome or early-onset aGvHD may not be able to be ruled out. Third, cytokine elevation was not associated with aGvHD in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL) 6 is one of the key cytokines involved in CRS after chimeric antigen receptor (CAR) T cell treatment, and the use of the monoclonal anti-IL6 antibody tocilizumab was effective in treating such CRS ( 11 , 12 ). With respect to CLSs in haplo-HSCT, several studies have demonstrated that IL6 was increased and the CLSs could be treated with methylprednisolone or tocilizumab ( 9 , 10 , 13 ). In phase I/II study, cyclosporine and mycophenolate mofetil given from day -1 instead of from day +5 in the PTCy model successfully diminished the incidence of early fever after graft infusion, further supporting an immune-based mechanism of fever and/or CLSs ( 14 ).…”
Section: Introductionmentioning
confidence: 99%